Aconitum Alkaloid Poisoning Because of Contamination of Herbs by Aconite Roots - Chan, Thomas Y. K (Phytotherapy research, 2016)
Aconitum alkaloid poisoning can occur after drinking decoction and soup made from non‐toxic herbs contaminated by aconite roots. In the present review, the main objective is to describe the clinical features, investigations and possible sources of contamination. A combination of neurological, gastrointestinal and cardiovascular signs and symptoms was seen. Ventricular tachyarrhythmias could occur in 18% of subjects. Yunaconitine and crassicauline A, mainly found in certain aconite roots from Southwest China, are most commonly involved. Herbal residues and unused herbs should first be inspected for gross contamination. On‐site inspection at the retailer should exclude accidental mix‐up or cross‐contamination when handling aconite roots. Samples of prescribed herbs are examined for gross contamination and analysed for the presence of Aconitum alkaloids. Samples of the implicated herb are also collected from the wholesaler for investigation. If post‐import contamination is unlikely, the regulatory authorities of the exporting countries should be notified for follow‐up actions. It is a challenging task to work out how non‐toxic herbs become contaminated by aconite roots. The source control with good agricultural and collection practices and quality assurance must be enhanced. Copyright © 2015 John Wiley & Sons, Ltd.